Perioperative Safety: Engage, Integrate, Empower, Sustain to Eliminate Patient Safety Events. Issue 6 (15th November 2021) - Falcone, Richard A.; Simmons, Jeffrey; Carver, Amanda M.; Mullett, Brooke; Kotagal, Meera; Lin, Erica; Muething, Stephen; von Allmen, Daniel
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: The perioperative environment is one of the most complex areas within a hospital with significant safety risks. Despite a long history of safety-focused work, a recent cluster of patient safety events prompted a renewed comprehensive approach to improve safety processes and transform culture. Methods: Our team comprehensively approached perioperative safety through integration across traditional silos and a focus on institutional safety culture. This approach consisted of a careful review of all events, developing Perioperative Safety Coordinating and Education teams, testing and implementing new/revised safety processes, and an ongoing evaluation plan. Results: Updates to our Perioperative Safety Mission and Tenets and the development of an empowered Safety Culture Champion team composed of a diverse group of frontline team members addressed our safety culture. In addition, key safety processes (time-outs, intraoperative huddles, and prevention of retained foreign bodies) were revised and implemented. Observation of key safety processes demonstrates a 90% compliance, which includes all steps and team engagement. After implementation, a span of 377 days between events was accomplished, which is significantly higher than the 33 days between events during our cluster. Conclusions: This work builds upon prior incremental improvements through a comprehensive investment in not only improving key processes but transforming the safety culture. Acceptable deviance from the standard process is no longer the norm. Instead, an approach that emphasizes understanding, integration, engagement, and accountability for safety by each team member for every patient, every time, every day, has been implemented.